Indonesia’s Nahdlatul Ulama and Muhammadiyah Students: A Study of The Book of Fiqh and its Impacts on Their Behavior - Habibillah, Putri; Ngadhimah, Mambaul (Proceedings of Annual Conference for Muslim Scholars, 2023)
Students who act in ways that are unethical and against the law often do so because of a lack of moral education, low religious value comprehension, environmental pressures, and the development of information and communication technology. This essay's objective is to assess the book's Fiqh and its effects on the behavior of students at the Muhammadiyah Modern Boarding School in Kediri and the NU Al-Falah Islamic Boarding School in Blitar. A mixed-methods strategy was used in this study; structured questionnaires were used to collect quantitative data, while structured questionnaires, in-depth interviews, non-participatory observation, and documentation were used to collect qualitative data. Using the ANOVA statistical analysis technique in SPSS 20.0, professionals assessed the construct validity and empirical validity. Condensing, displaying, and verifying qualitative data through the stages of analysis, as well as confirming the accuracy of the data through extending observations, stepping up persistence, triangulating, member checks, using reference materials, and having talks with coworkers. As a result of the study's findings, Students' behaviors at the NU Islamic Boarding School alter as a result of their study of the book of fiqh; nevertheless, students at the Muhammadiyah Islamic Boarding Schools show no such changes as a result of their study of the book of fiqh. Students' respect for the Kiai, Ustadz/Ustadzah, friendliness toward others, discipline, tolerance, and the ability to restrain themselves from inappropriate and dishonorable behavior are all indications of the dynamics of changes in the students' behavior.